All Days 2011
DOI: 10.2118/150791-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Strategies for Natural Gas Utilization: Niger Delta Case Study

Abstract: Nigeria is endowed with huge proven gas reserves estimated to be 184 trillion cubic feet (Tcf). It ranks as the seventh holder of natural gas reserves in the world, and the largest in Africa. Nigeria also flares more natural gas than any other country; it accounts for 12.5% of the world's annual gas flared equivalent to $2.0 billion of annual revenue wasted. There is crucial need, therefore, to reduce gas flaring and its environmental impacts, and to derive maximum economic benefits from gas production.The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The worsts are the release of GHGs and radioactive forcing (Cushing, et al, 2021), leading to severe irreversible climatic alterations that has attracted global attention in recent times. Clarion calls from several researchers (Ogbe, et al, 2011;Adekomaya, et al, 2016;Ogolo and Onyekonwu, 2015) on the urgent need to end the anthropogenic emissions from gas flaring need to be sustained towards a global attention to this ecological and climatic injustice. It is then the aim of this paper to join in the campaign of raising passionate appeals to stakeholders, opinion analysts and policy makers to join hands for remediating the already accrued carbon debt and other effects linked to gas flaring.…”
Section: Uchegbulam I; Aliyuda A; John Ymmentioning
confidence: 99%
See 3 more Smart Citations
“…The worsts are the release of GHGs and radioactive forcing (Cushing, et al, 2021), leading to severe irreversible climatic alterations that has attracted global attention in recent times. Clarion calls from several researchers (Ogbe, et al, 2011;Adekomaya, et al, 2016;Ogolo and Onyekonwu, 2015) on the urgent need to end the anthropogenic emissions from gas flaring need to be sustained towards a global attention to this ecological and climatic injustice. It is then the aim of this paper to join in the campaign of raising passionate appeals to stakeholders, opinion analysts and policy makers to join hands for remediating the already accrued carbon debt and other effects linked to gas flaring.…”
Section: Uchegbulam I; Aliyuda A; John Ymmentioning
confidence: 99%
“…Despite these waste gas recovery projects with operative gas master plans for a sustainable energy mix for Nigerians, bureaucratic bottlenecks on policymaking, regulations, enforcements and flare-out deadlines have created a gap between the expectations and realities. Even as more gas is flared in Nigeria than any other place in the world (Ogbe, et al, 2011;Akpomuvie, 2011;Oni and Oyewo, 2011;Tawari and Abowei, 2012;Anosike, 2010;Nwanya, 2011) showing her enriched natural gas reserves and potential benefits yet the country is among the 30 poorest nations with more than average of her citizens living below poverty line (Ukala, 2010;Nwanya, 2011).…”
Section: Uchegbulam I; Aliyuda A; John Ymmentioning
confidence: 99%
See 2 more Smart Citations
“…In Nigeria, a veterinary research finding by Ogbe et al [4], who reported that aqueous extract of the wild mushroom (Ganoderma sp) has anticoccidial effect against E. tenella infection in broiler chickens. Its health-promoting benefit was attributed to the presence of medicinally active bioactive compounds, minerals and amino acids [5,6]. In China and Japan, the cultivated specie (Ganoderma lucidum) is used as food supplement and as medicine to improve various parameters of health and immune functions in humans [7,8].…”
Section: Introductionmentioning
confidence: 99%